Eastspirit : transnational spirituality and religious circulation in east and west - Borup, Jørn. (International Studies in Religion and Society, 2017)
Mindfulness, yoga, Tantra, Zen, martial arts, karma, feng shui , Ayurveda. Eastern ideas and practices associated with Asian religions and spirituality have been accommodated to a global setting as both a spiritual/religious and a broader cultural phenomenon. 'Eastern spirituality' is present in organized religions, the spiritual New Age market, arts, literature, media, therapy, and health care but also in public institutions such as schools and prisons. Eastspirit: Transnational Spirituality and Religious Circulation in East and West describes and analyses such concepts, practices and traditions in their new 'Western' and global contexts as well as in their transformed expressions and reappropriations in religious traditions and individualized spiritualities 'back in the East' within the framework of mutual interaction and circulation, regionally and globally.